Pengembangan model pembelajaran tematik kelompok mata pelajaran Pendidikan Agama Islam berbasis artikulasi untuk mengembangkan keterampilan berfikir kritis siswa kelas X pada MAN I Kota dan MAN Sooko Mojokerto - Munib, Munib (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2016)
Articulation of cooperative learning model is one model of learning that can be used to improve student learning outcomes, especially on thematic learning. Because this model has several advantages, namely a student's readiness to train, train students' absorption, interaction easier.. The purpose of this research is the development of: Model making thematic learning groups of subjects of Islamic education based articulation that has been applied in MAN I Cities and Sooko MAN Mojokerto. Product Model thematic learning groups of subjects of Islamic education based articulation has been accomplished based analysis of trial data. Based on the measures that have been implemented can be concluded as follows. 1). Products are revised based on test results of theoretical and empirical are: assessment experts do not indicate a revision, but the results of the questionnaire, the revision by the student based on the questionnaire: (1) improving the use of resources in implementing the model (2) Changing the way the evaluation of the use of the model (3) Fix the model view or change the learning strategy. 2.) The products developed interesting for classical learning in the classroom and independently. 3) The product of these products can ease the burden of teachers in teaching. 4) The results of expert validation and testing, Model thematic learning groups of subjects based articulation of Islamic Education to develop critical thinking skills is fit for use for learning tematik.5) Products that are developed can increase students' motivation, and motivation is one of the conditions of the implementation of productive learning model in the form of thematic learning model subject groups based articulation of Islamic Education to develop critical thinking skills.